A REVIEW OF SPIRITUAL REMINISCENCE THERAPY FOR OLDER PEOPLE WITH MENTAL HEALTH PROBLEMS (Proceedings of the Global Public Health Conference, 2019)
Spiritual reminiscence therapy (SRT) is an intervention that involves evaluation of life experiences by sharing memories with others that guide individuals to understand the purpose of their life and future hopes. The effectiveness of SRT more specifically for older people needs greater interrogation before this intervention can be recommended. An integrative review of the literature was conducted to explore this question. The search involved published and unpublished studies using the keywords: spiritual reminiscence OR spiritual life review OR religious life review OR spiritual therapies AND older people OR older adults. The search strategy resulted in 847 studies from the electronic databases. Of the 847 studies, five met the inclusion criteria. Out of these five studies, three were quantitative studies, and two were qualitative studies. The evidence regarding the effectiveness of SRT was limited. Despite limited evidence from the quantitative findings, the qualitative findings suggested that SRT can be a worthwhile intervention for older people. Therefore, there is a need in future research to further understand SRT as an intervention for older people.
Keywords: spiritual reminiscence therapy; reminiscence therapy; older people